Two decades of student voice: reflections and the road ahead - Ayesha Verrall (New Zealand Medical Student Journal)
When starting the New Zealand Student Medical Journal (NZMSJ) 20 years ago, we were driven by a desire to support the professional development of New Zealand’s medical students, while building a platform to share their research and voices. As students, we struggled to and spaces where we could engage in meaningful discussions, share diverse opinions, and formally showcase our work. The journal became part of the solution—a forum where medical students could not only publish research but also explore current issues, emerging challenges and the future of healthcare.